Identification of the Load Profile in a Three-Phase Low Voltage Circuit (2021)
The quality of the power grid has become a very important aspect to measure the quality of the electric service, which implies greater interest in knowing the characteristics of the network, also having information about incidents makes it possible to analyze events, disturbances that stand out in the electrical system preventing the effects they cause. This article analyzes criteria for the evaluation of the load profile through the identification of the consumption signatures, carrying out the study of connected loads in a controlled environment, in order to propose a procedure for the identification of it, verifying the behavior of loads in an electrical grid.